Optimization of modularity during development to simplify walking control across multiple steps - Hinnekens, Elodie; Berret, Bastien; Morard, Estelle; Do, Manh-Cuong; Barbu-Roth, Marianne; Teulier, Caroline (Frontiers in Neural Circuits, 2024)
Walking in adults seems to rely on a small number of modules allowing to reduce the number of degrees of freedom that are effectively regulated by the central nervous system (CNS). While walking in toddlers seems to also involve a small number of modules when considering averaged or single-step data, toddlers produce a high amount of variability across strides, and the extent to which this variability interacts with modularity remains unclear. To address this matter, we compared the modular organization of toddlers and adults during several walking strides, with or without supporting toddlers to manipulate balance constraints. We recorded the electromyographic activity of 10 bilateral (lower limbs) muscles in adults (n=12) and toddlers (n=12) during 8 gait cycles and used non-negative matrix factorization to model the underlying modular command with the Space-by-Time Decomposition method. Significantly more computational modules were needed in toddlers to account for their greater stride-by-stride variability. Activations of these modules varied more across strides and were less parsimonious in toddlers than in adults, even when balance constraints were diminished. These findings suggest that the modular control of locomotion evolves between toddlerhood and adulthood, as the organism develops and practices. As variability persists when balance constraints are lowered, those findings are more likely to be linked to the ability to explore than to corrective mechanisms. As such, our results also suggest that new walkers can flexibly activate their motor command, and benefit from a higher space of possible actions, even though distinguishing between modular and non-modular inputs remains challenging.